Sustainable Interior Design for Urban Cafés: Integrating Urban Culture and Smart Technology to Enhance Work-Oriented Comfort - Setyaningrum, Ruth Puji; Pranajaya, I Kadek; Nutrisia Dewi, Ni Made Emmi (Malikussaleh University, Aceh, Indonesia, 2025)
The rise of urban culture and flexible work trends has redefined cafés as alternative workspaces, prompting the need for interior designs that are both sustainable and adaptive. However, many café environments still lack a holistic integration of local cultural values and emerging technologies to support prolonged, productive work. This study proposes a sustainable interior design model for urban cafés that combines cultural identity with innovative technological solutions to enhance user comfort. Using a qualitative methodology, the research involved field observations, semi-structured interviews, ergonomic evaluations, and digital environmental simulations, conducted in Renon, Denpasar—a vibrant urban area in Bali. Results indicate that incorporating cultural elements, such as material patterns, spatial layouts, and symbolic aesthetics, along with bright lighting, efficient ventilation, and ergonomic furniture, significantly improves functionality and user well-being. Users identified key comfort factors including lighting, furniture design, zoning, acoustics, and air quality. The study emphasizes the need for an interdisciplinary approach that fuses design engineering, local culture, and intelligent systems to create flexible, user-centered environments. Nine integrative design strategies are proposed to support both work productivity and cultural resonance. These findings provide practical insights for architects, designers, and café developers seeking to create meaningful and adaptable spaces in tropical urban settings. On a broader scale, the research contributes to the global discourse on non-traditional workspace design by presenting a replicable framework that aligns with sustainable urban development and the evolving work dynamics of the digital era.